CO2 quality control in Oxy-fuel technology for CCS: SO2 removal by the caustic scrubber in Callide Oxy-fuel Project. (August 2016) - Liu, Dunyu; Wall, Terry; Stanger, Rohan
Highlights: Both gas and liquid analysis were conducted on the caustic scrubber in COP. The Quencher captured most of SO2 while LP scrubber captured limited SO2 . Sodium is not effectively used in both Quencher and LP scrubber. Dynamic sulfur balance in the Quencher can be achieved. Final pH of discharged solution is dependent on the presence of HCO3 − . Abstract: Flue gas from Oxy-fuel combustion is enriched with CO2 and SO2 . SO2 has significant impacts throughout the system. This paper primarily focuses on the operation characteristics of caustic scrubber for the removal of SO2 in Callide Oxy-fuel Project. Both gas and liquid sampling and analysis were carried out for the caustic scrubber which comprises two spray columns, the initial Quencher followed by the low pressure (LP) scrubber. Dynamic changes of gas and liquid species in two scrubbers have been obtained and several conclusions can be drawn. From gas analysis, it can be concluded that the Quencher had high capture efficiencies for SO2 (97%) and NO2 (77%), and low capture efficiencies for NO (32%). The Quencher captured most of the SO2 and NO2 ; the LP scrubber captured a limited amount of SO2 (1%) and NO2 (4%). Therefore, the LP scrubber is not a necessary component for capturing SO2 . Liquid analysis gave consistent results with gas analysis in that the Quencher (0.011–0.037 M) contained a 100 times higher concentration of Total S than that (0.0001–0.0006 M) in the LP scrubber. The Total S existed in the form of S(IV) and S(VI) in the Quencher, and only in the form of S(VI) in the LP scrubber. The S(VI) ratio of 11% in the Quencher agreed with the reported 2–15% oxidation. SO2 concentration in gas phase can be correlated well with Total S in liquid, but not the effective ratio of Na + . Mass balance between gas and liquid Total S can be achieved. The long term storage of liquid samples is accompanied by pH changes and desorption of CO2 with exposure to the atmosphere. The final pH depends on the presence of HCO3 − . In the presence of HCO3 − in liquids, the final pH is around 8; in the absence of HCO3 −, the final pH is around 4. The increase in pH to 8 is explained by desorption of CO2 . The amount of CO2 desorbed is around 0.0614% of the amount of CO2 in the CPU.